2012
DOI: 10.1308/003588412x13171221588811
|View full text |Cite
|
Sign up to set email alerts
|

Pilocytic astrocytoma mimicking craniopharyngioma: a case series

Abstract: Although they are one of the most common brain tumours in childhood, piiocytic astrocytomas are rare in adulthood. We report a series of three piiocytic astrocytomas presenting as an intra/suprasellar mass in the fourth to sixth decades of life. All three radiologically mimicked the appearance of a craniopharyngioma, thus representing a potential radiological and diagnostic pitfall. In this series all three patients underwent successful operative management and have remained well throughout follow-up. The maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Typical radiographic findings of pilocytic astrocytomas are well known. Typical MRI findings of pilocytic astrocytomas are usually an enhancing mass with a non-enhancing cystic component [ 1 8 ]. Also, in general pilocytic astrocytomas are well-circumscribed and round [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Typical radiographic findings of pilocytic astrocytomas are well known. Typical MRI findings of pilocytic astrocytomas are usually an enhancing mass with a non-enhancing cystic component [ 1 8 ]. Also, in general pilocytic astrocytomas are well-circumscribed and round [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several supratentorial pilocytic astrocytomas mimicking other intracranial tumors have been reported. Skipworth et al [ 1 ] reported three suprasellar pilocytic astrocytomas mimicking a craniopharyngioma. A review of the literature revealed only one other case of supratentorial pilocytic astrocytoma mimicking a meningioma on preoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor biomarkers, such as beta-human chorionic gonadotropin and alpha-fetoprotein, may help to diagnose nongerminomatous germ cell tumors such as embryonal carcinoma, choriocarcinoma, endodermal sinus tumor. Although pilocytic astrocytomata are rare in adults, they mimic the appearance of craniopharyngiomata, which is a potential radiological and diagnostic pitfall [13].…”
Section: 2mentioning
confidence: 99%